Early-switch/early-discharge opportunities for hospitalized patients with methicillin-resistant Staphylococcus aureus complicated skin and soft tissue infections: proof of concept in the United Arab Emirates - El Houfi A (Infection and Drug Resistance, 2015)
Ashraf El Houfi,1 Nadeem Javed,2 Caitlyn T Solem,3 Cynthia Macahilig,4 Jennifer M Stephens,3 Nirvana Raghubir,5 Richard Chambers,6 Jim Z Li,7 Seema Haider81Dubai Hospital, Dubai, UAE; 2Rashid Hospital, Dubai, UAE; 3Pharmerit International, Bethesda, MD, USA; 4Medical Data Analytics, Parsippany, NJ, USA; 5Pfizer, New York, NY, USA; 6Pfizer, Collegeville, PA, USA; 7Pfizer, La Jolla, CA, USA; 8Pfizer, Groton, CT, USAObjectives: To describe real-world treatment patterns and health care resource use and to estimate opportunities for early-switch (ES) from intravenous (IV) to oral (PO) antibiotics and early-discharge (ED) for patients hospitalized in the United Arab Emirates (UAE) with methicillin-resistant Staphylococcus aureus (MRSA) complicated skin and soft tissue infections.Methods: This retrospective observational medical chart review study enrolled physicians from four UAE sites to collect data for 24 patients with documented MRSA complicated skin and soft tissue infections, hospitalized between July 2010 and June 2011, and discharged alive by July 2011. Data include clinical characteristics and outcomes, hospital length of stay (LOS), MRSA-targeted IV and PO antibiotic use, and ES and ED eligibility using literature-based and expert-validated criteria.Results: Five included patients (20.8%) were switched from IV to PO antibiotics while being inpatients. Actual length of MRSA-active treatment was 10.8±7.0 days, with 9.8±6.6 days of IV therapy. Patients were hospitalized for a mean 13.9±9.3 days. The most frequent initial MRSA-active therapies used were vancomycin (37.5%), linezolid (16.7%), and clindamycin (16.7%). Eight patients were discharged with MRSA-active antibiotics, with linezolid prescribed most frequently (n=3; 37.5%). Fifteen patients (62.5%) met ES criteria and potentially could have discontinued IV therapy 8.3±6.0 days sooner, and eight (33.3%) met ED criteria and potentially could have been discharged 10.9±5.8 days earlier.Conclusion: While approximately one-fifth of patients were switched from IV to PO antibiotics in the UAE, there were clear opportunities for further optimization of health care resource use. Over half of UAE patients hospitalized for MRSA complicated skin and soft tissue infections could be eligible for ES, with one-third eligible for ED opportunities, resulting in substantial potential for reductions in IV days and bed days.Keywords: IV-to-PO switch, length of stay, clinical criteria, antibiotic therapy, economics